Complete upper airway collapse and apnoea during tethered swimming in horses. (8th October 2019) - Jones, S.; Franklin, S.; Martin, C.; Steel, C.
Summary: Background: There is limited knowledge of the breathing strategy and impact on the patency of the upper respiratory tract (URT) in swimming horses. Objectives: To describe the respiratory responses and endoscopic appearance of the URT during tethered swimming in horses. Study design: Prospective descriptive study. Methods: Ten race‐fit horses, with no history of URT obstruction, were examined during tethered swimming. Endoscopic examination, heart rate, sound recordings and above and below water video recordings were obtained. Plasma lactate concentration was measured before and 5 min after swimming and tracheal endoscopy was performed 30 min after exercise to assess for presence of blood or mucus. Four horses also underwent endoscopy during exercise on the track. Results: Mean (±s.d.) breathing frequency was 28 ± 5 breaths/min during swimming, with a brief inspiration (mean ± s.d. TI  = 0.51 ± 0.08 s), followed by a period of apnoea (1.59 ± 0.53 s) and then a short, forced expiration (TE  = 0.42 ± 0.5 s). During apnoea all horses exhibited complete collapse of the URT including closure of the external nares, nasopharynx and rima glottidis (with bilateral adduction of the arytenoid cartilages and vocal folds) and, in two horses, epiglottic retroversion. No horses had URT collapse during overground exercise. Locomotor‐respiratory coupling was not observed during swimming. Median (IQR) plasma lactate post swim was 4.71 mmol/L (2.08–8.09 mmol/L) vs 0.68 mmol/L (0.65–0.71 mmol/L) preswim. Post swim endoscopy revealed grade 1 exercise‐induced pulmonary haemorrhage (EIPH) in 2 horses. Median mucus grade was 1 (range 0–3). Main limitations: Overground endoscopy was not performed in all horses. Conclusions: Horses experienced complete URT collapse associated with post inspiratory apnoea when swimming. The reason for this is unknown but may be to aid buoyancy or associated with the mammalian dive response – a survival reflex to preserve oxygen stores and prevent water entering the lungs.